Analysis of the impact of domestic politics in Georgia on its relations with the EU - Albert K. Dudaiti (Научно-аналитический вестник Института Европы РАН)
The article examines the complex and ambiguous influence of Georgia’s domestic policy on its relations with the European Union, highlighting contradictions between internal political processes and the expectations of Western partners. The primary aim of the study is to analyze key political decisions and their role in shaping the country’s image on the international stage, which in turn determines its prospects for European integration. The scientific significance of the article lies in critically rethinking the impact of geopolitical factors and domestic reforms, which, despite their declarative nature, often face institutional and societal barriers. The methodology is based on the study of official documents, analytical reviews, and a comparative analysis of political transformations and sociological survey data. The results demonstrate that, in the context of domestic instability and external pressures, significant emphasis is placed on the formation of an effective political course that reflects national interests. The article underscores the necessity of striking a balance between orientation towards the EU and strengthening the country’s sovereignty. The practical significance of the study lies in the formulation of recommendations aimed at enhancing the effectiveness of Georgia’s foreign policy and adopting a more balanced approach to interaction with the EU.